Is It Legal to Provide Liquidity on the Vexanium Decentralized Exchange in Indonesia? - Multazam, Mochammad Tanzil; Huzairin, Regita Amanah; Pratama, Sandika Putra; Irwansyah, Irwansyah (Yustisia, 2023)
One of the platforms in the blockchain is a decentralized exchange. The existence of these platforms helps exchange crypto assets instantly in the blockchain ecosystem without having to exchange them at a central exchange. The liquidity guarantors of decentralized exchanges are liquidity providers. This study aims to assess liquidity providers' legal safety on Vexanium, Indonesia's first public blockchain. The normative method employed in this analysis of the laws and regulations related to blockchain in Indonesia involves a preliminary examination of the liquidity provision process. This study found that the decentralized exchange platform on the Vexanium blockchain still needs to meet the criteria as an electronic system following the laws and regulations. In addition, the absence of clear information about the parties in the platform makes the liquidity provision contract voidable. This research can be utilized for platform developers in the Vexanium blockchain to pay more attention to legal aspects in creating their platforms..